(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
Kite Runner is a fictional story that combines the strange story of a small child with the beginning of the conflict that occurred in Afghanistan. Marked by the fall of the monarchy system and the intervention of the Soviet Union, these events become the backdrop that changes the main character’s life. The purpose of this study was to determine the character and moral values ​​of the kite runner novel. There are two types of data sources in this study, namely primary data and secondary data. Researchers use direct observation through novels and any information documents. The results of this study indicate that theoretically this research is able to elaborate on the characteristics of the main character and explain the moral message that the author wants to convey to the reader through the kite runner novel. This study uses a qualitative method. The data obtained using data collection techniques in the form of novels, and various sources of document information. Qualitative methods are descriptive research and tend to use analysis. The results of this study show the character in the novel that amir, the main character, is the son of a wealthy person in Afghanistan, he has girls who always obey him. The things he wanted to ask for help, Hassan never disobeyed his orders. Remembering Hassan has shown total respect to Amir. He was free to make Hassan as he wished. While the moral message that wants to be conveyed to the readers in this novel is to do the right thing, which includes caring, forgiving, helping, honest and brave.